Control and Sexuality: The Revival of Zina Laws in Muslim Contexts - Hamzić, Vanja; Mir-Hosseini, Ziba (Women Living Under Muslim Laws, 2010)
This book examines zina (adultery) laws in Indonesia, Iran, Nigeria, Pakistan and Turkey, as well as in their broader historical context within the Islamic legal tradition, in order to explore connections between the criminalisation of sexuality, gender-based violence and women's rights activism. "It is most timely that this publication should emerge when issues of culture and human rights are being debated in many venues in the international arena: within the United nations; in national and transnational, mainstream and alternative media outlets; and across social and political movements." (Farida Shaheed, UN Independent Expert on Cultural Rights)